Analisis Dampak Struktur Modal, Likuiditas, dan Pertumbuhan Penjualan Terhadap Financial Distress Pada Perusahaan Sektor Ritel di BEI - Aulia Nuraini; Emmy Indrayani (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This research is a quantitative study that aims among others to determine and analyze the effect of capital structure, liquidity, and sales growth on financial distress. The sample used in this study is a retail sector company listed on the Indonesian Stock Exchange for the period 2021 – 2023. For sampling technique used in this research a purposive sampling method, was used obtained many as 14 companies with a total of 31 observations. Hypothesis testing in this study was carried out by partial test (T test) and simultaneous test (F test) and classical assumption test using IBM SPSS 26. The result of this study indicate that (1) capital structure has a negative effect on financial distress, (2) liquidity has an effect on financial distress, and (3) sales growth has no significant effect.